The Use of Internet Purchasing Among Postgraduate Students in UUM - Etturki, Tareg A. Yousef (2008)
The general purpose of this study was to find out whether a relationship between attitudes, subjective norm, perceived behavioral control and Internet purchasing of postgraduate students. The significant positive relationships between attitudes, subjective norm, perceived behavioral control and internet purchasing offer a clear indication of the importance of features to explain consumer purchase behavior. Hence, this study aims to propose, operationalize, and empirically examine an extended model (i.e. with the inclusion of self-identity) that explains and predicts consumer purchase behavior. The result of correlation, linear regression and multiple regressions in assessing the variables or the empirical relationship between attitudes, subjective norm, perceived behavioral control contribute were positively related to behavior as hypothesized. The positive association among all independent variables to dependent variable (adj.r2=80%) was supported.